Tropical living : contemporary dream houses in the Philippines - Reyes, Elizabeth. 4 0 16; 5 (Singapore : Periplus, 2000)
Photographs and brief text showcase thirty contemporary residental designs found in the Philippines, representing various styles, including the homes of artists, villas, manors, and more.
Adult;Adult
Keywords: 2 -- 0; 6; Interior decoration;Interior design -- Philippines.;Philippines.; 20; 2